Novel Left Heart Catheterization Ramp Protocol to Guide Hemodynamic Optimization in Patients Supported With Left Ventricular Assist Device Therapy. Issue 4 (19th February 2019) - Rosenbaum, Andrew N.; Frantz, Robert P.; Kushwaha, Sudhir S.; Stulak, John M.; Maltais, Simon; Behfar, Atta
Abstract : Background: Left ventricular (LV) hemodynamic assessment has been sparsely performed in patients supported on continuous‐flow LV assist devices (cfLVADs). Insight into dynamic changes of left heart parameters during ramp studies may improve LV assist device optimization and evaluate pathology. Methods and Results: To complement right heart catheterization, a novel technique for left heart catheterization in patients with a cfLVAD was developed. Patients implanted with cfLVADs underwent hemodynamic ramp left heart catheterization and right heart catheterization with transthoracic echocardiography. Continuous aortic and LV pressures were measured along with right atrial, pulmonary artery, and pulmonary capillary wedge pressures. A novel index, the transaortic gradient (TAG) was established. Thirty eight patients with cfLVADs were evaluated at a median of 446 days (interquartile range, 183–742) after device implant. During left heart catheterization performed for hemodynamic optimization, drop‐in LV end‐diastolic pressure and pulmonary capillary wedge pressure were associated with a rise in TAG. A range was identified for TAG (20–40 mm Hg) as providing the most optimal level of hemodynamic offloading. Pathologic states deviated from normal responses to ramp. LV assist device thrombosis was associated with an inability to increase in TAG during speed ramp. Significant aortic insufficiency was associated with a marked increase in LV end‐diastolic pressure despite a concomitant decrease in pulmonary capillary wedge pressure with increasing LV assist device speeds. Conclusions: Inclusion of left heart catheterization to a typical right heart catheterization LV assist device ramp protocol imparted unique insights to optimize cfLVAD speeds in different clinical scenarios. A novel index, the TAG was defined and provided additional resolution to optimized offloading.